(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to conduct a systematic review of the cost-effectiveness of Prasugrel in acute coronary syndrome population. Method: A systematic review approach was used to identify studies from databases that evaluated the cost-effectiveness of Prasugrel compared with other P2Y12 receptor inhibitors in acute coronary syndrome patients. Results: A total of eight studies were included in the review. The findings indicate that Prasugrel helps reduce burden of cardiovascular mortality (YLL 0.144 vs. 0.151), increase quality-adjusted life years (QALY 5.03 vs. 4.94), and lower rehospitalization costs compared with Clopidogrel. The incremental cost-effectiveness ratio ranged from USD/EUR 996 to 14,350 per QALY, all of which were below the willingness-to-pay thresholds. However, differences in economic and healthcare background across countries should be considered, and some findings may reflect model assumptions rather than real-word data. Conclusion: Within the scope of this review, both Ticagrelor and Prasugrel were found to be more cost-effective than Clopidogrel, while clear comparative evidence between Ticagrelor and Prasugrel remains limited. Future research should focus on direct head-to-head comparisons between Prasugrel and Ticagrelor, and policy makers should consider incorporating Prasugrel into the Vietnamese health insurance reimbursement